A composition for diabetic wound treatment - Fakurazi, Sharida; Abas, Faridah; Ahmad, Zalinah; Amali, Abubakar Muhammad; Arulselvan, Palanisamy (2013)
The present invention relates to a composition for diabetic wound treatment, characterised in that the composition comprises quercetin glucoside, kaempferol glucoside and vicenin 2 bioactive compounds.